Analisis Faktor-Faktor yang Berpengaruh Terhadap Pengelolaan Sampah di Bank Sampah RW 7 Gunung Anyar Tambak Menggunakan Pemodelan Sistem Dinamis - Mohamad Mirwan; Mar'atus Sholikhah (Prosiding ESEC, 2023)
Bank Sampah Sumber Dana is one of the waste banks in RW 7 Gunung Anyar Tambak and is a supporting institution for ProKlim in that RW. The aim of the research is: (1) Identifying factors that influence the sustainability of the waste bank; (2) Formulate the relationship between the factors that influence the creation of a dynamic system model; (3) Analyze the factors that influence the sustainability of the waste bank. This research is a qualitative research with combined data collection techniques (quantitative and qualitative data). In this research, a dynamic system is used to create models and predict the obstacles that will be faced by looking at the influencing factors. To perform simulations with dynamic systems, Stella software is used. The first step is to identify the management system of Bank Sampah Sumber Dana into several sub-systems. Then it was made into a CLD and SFD model. The analysis results were obtained from analyzing the variables in the model and it can be concluded that overall the management system is running quite well. This is supported by the efforts of the waste bank management so that the community has a good interest in managing waste from its source.